Вынесите за скобки общий множитель:
(x+y)+ a(x+y)-2 (x+y)=(x+y) (...)
m (a-b)-n(b-a)+(3a-3b)=(a-b) (...)
(2m-6n)+(xm-3xn) -y(3n-m)=(m-3n) (...)
(6x-15y)-(5y-2x) +(2ax-5ay)=(2x-5y) (...)
(-am-bm)+(3a+3b)-(x^2a+x^2b)=(a+b) (...)

2

Ответы и объяснения

2014-02-04T18:20:34+00:00
1. = (x+y)(1+a-2)
2. =(a-b)(m+n+3)
3. =(m-3n)(2+x+y)
4. =(2x-5y)(3+1+a)
5. =(a+b)(-m+3-x²)
2014-02-04T18:23:45+00:00
Если не против я пример переписывать не буду
1) (х+у)(1+а–2)=(х+у)(–1+а)
2) (а–в)(m+n+3)
3) (m–3n)(2+x+y)
4) (2x–5у)(3+1+а)=(2х–5у)(4+а)
5) (а+в)(–1+3–х^2)